A - Browning, W.R.F. (Oxford University Press, 2004)
This revised edition is the most authoritative, accessible, and up-to-date dictionary of the Bible available in paperback. As well as providing helpful information about important places and personalities, it is particularly concerned to expound the themes and doctrines of the Bible and to indicate their status in the light of modern scholarship. With entries ranging from earthquakes and mice to feminism and the Dead Sea Scrolls, the dictionary is a lively and absorbing reference work for all readers of the Bible